Emission trading restrictions with endogenous technological change - Marzio Galeotti; Paolo Buonanno; Carlo Carraro; Efrem Castelnuovo (Fondazione Eni Enrico Mattei (FEEM), 2000)
In this paper we use a simple climate model with endogenous environmental technical change in order to analyse the effects on equity and efficiency of different degrees of restrictions on trade in the market for pollution permits. The model is obtained by incorporating in Nordhaus and Yang (1996)'s RICE model the notion of induced technical change as proposed in Goulder and Mathai (1998). With the help of such model we aim at assessing the pros and cons of the introduction of ceilings on emission trading. In particular, we analyse the implications of restrictions on trading both in terms of their cost effectiveness and in terms of their distributional effects. The analysis takes into account the role of environmental technical change that could be enhanced by the presence of ceilings on trading. However, this effect is shown to be offset by the increased abatement cost induced by the larger than optimal adoption of domestic policy measures when ceilings are binding. Hence, our analysis provides little support in favour of quantitative restrictions on emission trading even when these restrictions actually have a positive impact on technical change. Even in terms of equity, ceilings find no justification within our theoretical and modelling framework. Indeed, we find that flexibility mechanisms in the presence of endogenous technical change increase equity and that the highest equity levels are achieved without ceilings, both in the short and in the long run.
Keywords: H0; H2; H3; 330; Climate policy; environmental modelling; integrated assessment; emission trading; technical change; ceilings; Klimaschutz; Emissionshandel; Umweltabkommen; Technischer Fortschritt; Forschung; Theorie